The Influence of Human Resources, Use of Information Technology and Public Participation to the Transparancy and Accountability of Village Financial Management (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aims to examine and obtain empirical evidence on partial evidence of the influence of Human Resources, Use of Information Technology and Public Participation on Transparency and Accountability of Village Financial Management in East Praya District, Central Lombok Regency. Type of research is explanatory method with purposive sampling method. It retrieved by 55 respondents, who are the core of the village, members of BPD and communities willing to provide information on village financial management. Data analysis is SmartPLS 3.0. The results of this study indicate Human Resources, Use of Information Technology and Public Participation have a significant positive effect on Transparency and Accountability of Village Financial Management in East Praya Subdistrict. This research is expected to be able to give contribution to Local Government, Village Government and society in order to have the better level of transparency and accountability of village financial management as one effort to improve prosperity of society in East Praya Sub-district